Introduction to microelectromechanical systems engineering - Maluf, Nadim (Microelectromechanical systems series., 2004)
Bringing you up-to-date with the latest developments in MEMS technology, this major revision of the best-selling An Introduction to Microelectromechanical Systems Engineering offers you a current understanding of this cutting-edge technology. You gain practical knowledge of MEMS materials, design, and manufacturing, and learn how it is being applied in industrial, optical, medical and electronic markets. The second edition features brand new sections on RF MEMS, photo MEMS, micromachining on materials other than silicon, reliability analysis, plus an expanded reference list.